2020
DOI: 10.1097/pcc.0000000000002350
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Dexmedetomidine for Prolonged Sedation in the PICU: A Prospective Multicenter Study (PROSDEX)*

Abstract: Objectives: We sought to evaluate dexmedetomidine efficacy in assuring comfort and sparing conventional drugs when used for prolonged sedation (≥24 hr) in critically ill patients, by using validated clinical scores while systematically collecting drug dosages. We also evaluated the safety profile of dexmedetomidine and the risk factors associated with adverse events. Design: Observational prospective study. Setting: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 37 publications
0
37
0
2
Order By: Relevance
“…Dexmedetomidine assured comfort, spared use of other sedatives, and attenuated withdrawal and delirium symptoms. The loading dose and infusion dosages of dexmedetomidine were independent risk factors for hemodynamic adverse events [ 168 ].…”
Section: Sedationmentioning
confidence: 99%
“…Dexmedetomidine assured comfort, spared use of other sedatives, and attenuated withdrawal and delirium symptoms. The loading dose and infusion dosages of dexmedetomidine were independent risk factors for hemodynamic adverse events [ 168 ].…”
Section: Sedationmentioning
confidence: 99%
“…The recently published clinical practice guidelines for the management of Pain, Agitation, Neuromuscular Blockade, and Delirium in critically ill pediatric patients with consideration of the PICU Environment and Early Mobility (PANDEM) and the Recommendations for analgesia and sedation in critically ill children admitted to intensive care unit [ 8 , 19 ] both recommend the use of alpha 2 -agonists over benzodiazepines as a first-line sedative. It has been shown that alpha 2 -agonists is a safe and benzodiazepine sparing alternative for sedation in the pediatric population [ 20 22 ]. We could reveal that only as much as 11% of the responding PICUs in Europe would use dexmedetomidine as a first-choice sedative and only 7% opted for clonidine.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this study also showed that the WAT-1 score significantly decreased at 24 h of DEX infusion by a median of 2 points (interquartile range (IQR), 1-4), and the prevalence of WS decreased from 19% to 2% after start of DEX infusion (p < 0.001). 23 These promising results certainly encouraged the design of this randomized clinical trial in the attempt to add further supporting evidence to the current knowledge for the use of DEX as an adjunctive treatment for WS. However, it may be appropriate to specify that the outcome measures of the PROSDEX study were evaluated at a single 24-hour timepoint, whereas in our F I G U R E 2 Study flow chart.…”
Section: Discussionmentioning
confidence: 95%
“…Overall, there were no AEs requiring intervention other than the DEX discontinuation, and this is consistent with what was described in previous studies. 23 However, less severe events, mostly bradycardia and/or hypotension, were recorded among patients in the DEX arm which led to DEX discontinuation and drop-out from the study. Thus, our study confirms that DEX infusion could be considered overall relatively safe; however, in some patients, there could be a particularly intense hemodynamic response, with the possible need to suspend the infusion.…”
Section: Discussionmentioning
confidence: 98%